Structural and Functional Changes in The Kidneys and Heart in Patients with Chronic Heart Failure with Anemia - A., Xalilova F. (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
Renal fibrosis markers were evaluated in dynamics to study specific changes in the kidneys of patients with different hemodynamic types and functional classes of chronic heart failure with anemia and to evaluate the effectiveness of complex treatment. Renal fibrosis marker cystatin C in the blood was 2591.0 ± 108.4 and 755.0 ± 18.87 pg / ml, respectively, in chronic heart failure with anemia and without anemia (p˂0.001). This was indicative of a fibrosis process occurring in the kidney. After complex treatments with the addition of iron, the cystatin C index decreased by 2.25 times (p˂0.001), the clinical condition, quality of life and endurance to physical activity changed significantly positively.